2015
DOI: 10.3897/zookeys.518.6127
|View full text |Cite
|
Sign up to set email alerts
|

Cherax snowden, a new species of crayfish (Crustacea, Decapoda, Parastacidae) from the Kepala Burung (Vogelkop) Peninsula in Irian Jaya (West Papua), Indonesia

Abstract: A new species, Cherax snowden sp. n., from the Oinsok River Drainage, Sawiat District in the central part of the Kepala Burung (Vogelkop) Peninsula, West Papua, Indonesia, is described, figured and compared with the closest related species, Cherax holthuisi Lukhaup & Pekny, 2006. This species is collected and exported for ornamental purposes and its commercial name in the pet trade is “orange tip” or “green orange tip”. Both species may be easily distinguished morphologically or by using sequence divergence, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…The other group contains species that have the rostral and sometimes the median carina well developed and referred to as the Astaconephrops group with Nobili’s (1899) Astaconephrops albertisii as the type. Newly described species have been placed into one or the other of the two subgenera (Lukhaup and Pekny 2006; Lukhaup and Pekny 2008; Lukhaup and Herbert 2008; Lukhaup 2015, Lukhaup et al 2015; Patoka, Blaha and Kouba 2015). Munasinghe et al (2004a, b), Austin (1996); and Austin et al (1996) however, identified three geographically-based lineages within Cherax based on molecular genetics and phylogenetic studies.…”
Section: Systematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other group contains species that have the rostral and sometimes the median carina well developed and referred to as the Astaconephrops group with Nobili’s (1899) Astaconephrops albertisii as the type. Newly described species have been placed into one or the other of the two subgenera (Lukhaup and Pekny 2006; Lukhaup and Pekny 2008; Lukhaup and Herbert 2008; Lukhaup 2015, Lukhaup et al 2015; Patoka, Blaha and Kouba 2015). Munasinghe et al (2004a, b), Austin (1996); and Austin et al (1996) however, identified three geographically-based lineages within Cherax based on molecular genetics and phylogenetic studies.…”
Section: Systematicsmentioning
confidence: 99%
“…The crayfishes of the island of New Guinea were extensively studied by Holthuis (1949, 1956, 1958, 1982, 1986, 1996), with additions by Lukhaup and Pekny (2006, 2008a), Lukhaup and Herbert (2008), Lukhaup (2015), Lukhaup et al (2015) and Patoka et al (2015). Nevertheless, over the last decade, there has been an increasing number of colourful crayfish, presumed to be a further undescribed species, sold from New Guinea in the ornamental fish trade in Europe and Asia under the names Cherax “irian jaya” and Cherax “hoa creek” (Lukhaup and Pekny 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The crayfishes of the island of New Guinea were extensively studied by Holthuis (1949, 1956, 1958, 1982, 1986, 1996), with recent additions by Lukhaup and Pekny (2006, 2008a) and Lukhaup and Herbert (2008). Nevertheless, over the last decade, there has been an increasing number of colourful crayfish sold in the ornamental fish trade in Europe, North America, and Asia under the names Cherax ”Hoa Creek”, ”Blue Moon”, and “Irian Jaya” presumed to represent a further undescribed species from New Guinea (Lukhaup and Pekny 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Since 2000, at least eight species or forms, mostly from the island of New Guinea, have been found in the pet trade before they were formally described scientifically: Procambarus fallax f. virginalis (Scholtz et al, 2003), Cherax holthuisi (Lukhaup & Pekny, 2006), Cherax boesmani (Lukhaup & Pekny, 2008), Cherax peknyi (Lukhaup & Herbert, 2008), Cherax pulcher (Lukhaup, 2015), Cherax gherardiae (Patoka et al, 2015a, Patoka et al, 2015b, Cherax snowden , and Cherax subterigneus (Patoka et al, 2015a). Given the recent descriptions of these species, with several species names appearing in a short time frame (two descriptions were published while this paper was being reviewed), it would not be surprising if the taxonomic status of some of these species will be revised in the future.…”
Section: New Crayfish Discovered In the Pet Tradementioning
confidence: 99%